PENGARUH PEMAHAMAN KARYAWAN ATAS PERHITUNGAN, PEMOTONGAN DAN PELAPORAN PAJAK PENGHASILAN ORANG PRIBADI DALAM NEGERI TERHADAP KETAATAN DALAM PERPAJAKAN PADA PT.GAG NIKEL - Martha Carolina (Universitas Bunda Mulia, 2017)
Based on the results of research done on the PT Gag Nikel, its appears that there are still many employees above of non – taxable income does not understand how to calculate and report income tax an individual taxpayer. Based on this the authors make the point as follows